Papel do oxalato na neuropatia sensitiva periférica induzida por oxaliplatina em camungondos : comparação entre a oxaliplatina e seu análogo livre de oxalato - Pereira, Anamaria Falcão (2015)
Oxaliplatin (OXL) is a third generation platinum compound with potent cytotoxic activity against several types of cancers, having a side effect is difficult to treat, a severe peripheral neuropathy. Studies suggest that oxalate, OXL metabolite, is involved in the development of peripheral sensory neuropathy (PSN); so that was published the synthesis of an OXL analogue (LLC-1402), oxalate free, which has antitumor properties (LIU et al., 2013). The objective of this research is to study the role of oxalate in OXL induced neuropathy in mice, comparing OXL with LLC-1402. The PSN was induced by two injections (iv.) OXL (2 mg/ kg) per week, in male Swiss mice, for 4 ½ weeks, totaling 9 injections. LLC-1402 (7, 14 and 28 mg / kg) was administered (iv.) following the same scheme. Nociceptive tests were performed (electronic von Frey and tail immersion test) weekly. After, it was chosen dose of 14 mg / kg of the LLC-1402 to perform another experiment, in which was added oxalate injection (1.7 mg/kg). In the 28th day, it was made blood collection for total leukocyte count and biochemical measurement. In the 28th and 56th days, spinal cord and DRG were removed for immunofluorescence for ATF-3, c-FOS, iNOS and NeuN. The results showed that both OXL and LLC-1402 were able to decrease the paw withdrawal threshold and tail withdrawal time significantly (p<0.05) compared to the control group. The injection of LLC-1402 together with oxalate and only oxalate was also able to reduce the paw withdrawal threshold and the tail withdrawal time. Moreover, all groups treated with OXL, LLC-1402 and oxalate showed a significant reduction in the total leukocyte count. The biochemical measurement (glutamic oxaloacetic transaminase, glutamic pyruvic transaminase, urea, creatinine) showed no statistical difference between the groups. The results also showed increased c-Fos immunoexpression in GRD in groups treated with OXL, LLC-1402 and LLC-1402 together with oxalate in the 28 and 56 days, and only oxalate the 28th day. This increase was observed in the dorsal horn of the spinal cord at 28th day in all the treated groups. It was not observed this increase in the dorsal horn of the spinal cord in the 56th day. It was observed an increase in immunoexpression of ATF3 in DRG and spinal cord of dorsal horn in all treated groups in the 28th and 56th days. iNOS immunofluorescence showed no significant difference between groups in the DRG nor spinal cord, already in the 28th day, there was an increase in immunoexpression of iNOS in GRD. Thus, the results showed that the oxalate may be partially involved in PSN induced OXL.